Una raccolta di sogni durante la pandemia: aspetti sociali e interpretativi - Fargnoli, Domenico; Bisconti, Paola; Fargnoli, Francesco (Il sogno della farfalla, 2021)
Covid-19 pandemic has affected the whole world, leading to radical changes in social habits due to the periods of lockdown, social distancing and infection prevention and to the impact that the emergency has had on health care workers. The authors of this paper discuss the result of an online survey administered to 780 people between May and June 2020. Through the analysis of 280 dreams gathered in the research, the authors investigate whether these changes due to the outbreak of the pandemic have had a significant effect on people’s psychic life. Finally, the paper consider how the interpretation of dreams through a sociological lens can lead to a deeper understanding of these changes.